Pembelajaran Mitigasi Bancana Di PAUD - Yeni Lestari, Ni Gusti Ayu Made; Marsono; Suyanta, I Wayan; Septiari Dewi, Putu Ayu; Hari Raditya Cahyani, I Dewa Ayu Agung (Jurnal Ilmiah POTENSIA, 2025)
Disaster mitigation education is critically important to introduce from an early age, as young children are among the most vulnerable populations during disasters. This study aims to examine the implementation of disaster mitigation education in early childhood education (ECE) settings and identify teachers' needs in delivering disaster-related content to young learners. A survey method was employed involving 67 ECE teachers in Badung Regency. Data were collected through a Google Forms questionnaire distributed via WhatsApp and analyzed using descriptive quantitative analysis. The findings revealed that only 11.9% of teachers frequently conduct disaster response simulations with children, while 19.4% rarely conduct them, 62.7% occasionally, and 6% never. Regarding content coverage, 89.4% of teachers include both pre-disaster and during-disaster phases in their instruction, while 10.6% focus solely on the during-disaster phase. The disaster simulation types implemented include earthquakes (77.6%), fires (9%), floods (7.5%), and volcanic eruptions (4.5%), while 1.4% of teachers do not include any disaster simulations. Additionally, 98.5% of teachers expressed the need for technology-based and interactive disaster mitigation learning media, while only 1.5% considered traditional simulations adequate. The study concludes that introducing disaster mitigation education at an early age can equip children with essential knowledge and skills for effective disaster response. Therefore, engaging and contextually relevant learning media and activities are crucial for enhancing disaster preparedness education in early childhood settings.